The Effect of Digital Literacy Ability and Learning Independence on Students' Creative Thinking in Economics Subjects - Nofia Firdayanti; Gusnardi Gusnardi; Hendripides Hendripides (CV. Rayyan Dwi Bharata, 2023)
This article is a type of quantitative descriptive research that aims to find out whether digital literacy abilities and independent learning affect students' creative thinking in economics subjects. The method used in this research is a quantitative descriptive method. The population in this study were all students of class XI IPS at SMAN 15 Pekanbaru, totaling 144 students. The sample of this research is 36 students with purposive sampling technique. The instruments used to collect data were creative thinking tests, digital literacy ability questionnaires and independent learning. The data analysis technique used is multiple regression analysis. The results of this study indicate that: 1) there is an influence of digital literacy skills on creative thinking where the digital literacy ability variable shows a significance value of Sig. 0.017 0.05 and the results of the t test obtained t count 2.518 t table = 2.034. 2) there is an effect of independent learning on creative thinking where the digital literacy ability variable shows a significance value of 0.008 0.05. Then the results of statistical calculations t-count = 2.826 t-table = 2.034. 3) digital literacy skills and learning independence simultaneously have a significant effect on creative thinking by 49.2%. The remaining 50.8% is influenced by variables other than the variables examined in this study.